G-CSF mediated neutrophil augmentation in a unique case of comorbid idiopathic Parkinson's disease and treatment-resistant schizophrenia on clozapine - Olivia Morrow; Lucy Gibson; Manraj Bhamra; Anthony S. David; Sotirios Posporelis (SAGE Publishing, 2020)
Treatment of psychosis in Parkinson's disease (PD) is challenging; pharmacological options are limited, with clozapine considered most effective. The risk of agranulocytosis restricts the use of clozapine, but, where this occurs, cautious re-challenge with granulocyte stimulating factor can be successful. We present a unique case of a patient who developed early-onset PD on a background of antecedent treatment-resistant schizophrenia, who had been treated effectively with clozapine for over 15 years with no adverse events. However, during a hospital admission intended to optimise her Parkinsonian medications, she developed persistent neutropenia necessitating clozapine discontinuation. Numerous attempts to re-challenge with clozapine failed until augmentation with lithium and G-CSF was trialled. Two doses of G-CSF led to a sustained increase in the neutrophil count, allowing the continuation of clozapine therapy in the 1 year of follow up. This illustrates the potential for G-CSF to be used to facilitate clozapine use in a patient population not described previously. Neutrophil augmentation allowed the sustained continuation of this effective therapy, treating her psychotic symptoms without detriment to her movement disorder. We suggest that G-CSF might be considered as a treatment option in other cases where clozapine-associated neutropenia obstructs its use.